An in-vitro study to evaluate the accuracy of dies obtained from dual arch impression trays using addition silicone impression material and tray combinations (Health Renaissance, 2015)
Background: Dual-arch impression technique allows the simultaneous recording of  tooth preparation, opposing anatomic tooth and maxillomandibular relationship. The  accuracy of reproduction of this easy and quick technique, however, has not been  studied in detail in past. Objective: To compare the accuracy of the impressions  made by using the same impression material in dual arch plastic trays, dual-arch  metal trays and acrylic resin custom trays. Methods: The dies obtained from the  addition silicone impressions made in dual-arch plastic trays, dual-arch metal trays  and full arch acrylic resin custom trays were compared for the dimensional accuracy  with the prepared typodont tooth as a control. Student’s paired t-test and unpaired  t-test were used for the data analyses using the Statistical Package for Social Studies  (SPSS) version 11.5. Results: The dies obtained from all the impression combinations  showed increased dimension (acrylic resin custom trays 9.4 mm±0.048, dual-arch  plastic trays 9.5 mm±0.035, dual-arch metal trays 9.41 mm±0.017) as compared to  the dimension of control (9.39 mm±0.007). Conclusion: All the tray-impression  material combinations showed variable accuracies. Full arch acrylic resin trays  resulted in greatest accuracy whereas dual-arch plastic trays the least accuracy.Health Renaissance 2014;12(2):  pp: 111-117